Ocorrência de cristais em plantas medicinais utilizadas no tratamento da nefrolitíase: Paradoxo? - Augusto Scardelato, Juhan [UNESP]; Pella Legramandi, Victor Hugo [UNESP]; do Sacramento, Luis Vitor Silva [UNESP] (My University, 2013)
Nephrolithiasis (kidney stones) can be seen as a common clinical condition responsible for substantial economic, social and psychological costs, due to its high morbidity, especially since it affects adults in their productive phase. Its development in the urinary tract is a complex and multifactorial process. The majority of kidney stones are made of calcium oxalate. A lot of plants are used to treat nephrolithiasis and they often exhibit calcium oxalate crystals in the parts that are employed for this medicinal purpose, representing a possible risk. In this light, we performed a literature review via the databases Scielo, PubMed and Medline and found 28 articles reporting the traditional use of plants in the treatment of nephrolithiasis. The occurrence of calcium oxalate crystals was indicated in 19 species. We argue that the use of these plants could give rise to adverse effects in people who are prone to form calcium oxalate stones in the kidney.

A nefrolitíase pode ser vista como uma condição clínica frequente responsável por importante ônus econômico, social e psicológico, decorrente de sua elevada morbidade, especialmente por se manifestar em adultos em fase produtiva. O seu desenvolvimento no sistema urinário é um processo complexo e multifatorial. Em sua maioria, os cálculos renais são compostos por oxalato de cálcio. Diversas espécies vegetais são empregadas no combate à litíase renal e frequentemente apresentam cristais de oxalato de cálcio nas partes empregadas para esta finalidade medicinal, podendo originar riscos. Desta forma, foi realizada uma revisão de literatura nos indexadores Scielo, PubMed e Medline, nos quais encontraram-se 28 registros relatando o uso tradicional de plantas no tratamento de litíase renal, sendo apontada a ocorrência de cristais de oxalato de cálcio em 19 espécies. Argumenta-se que a utilização destas pode acarretar possíveis efeitos indesejados em indivíduos propensos à formação de cálculos de oxalato de cálcio nos rins. Palavras-Chave: Nefrolitíase. Plantas medicinais. Oxalato de calico. Etnobotânica.
Occurrence of crystals in medicinal herbs for the treatment of nephrolithiasis: A paradox?
Keywords: Calcium oxalate; Ethnobotany; Medicinal plants; Nephrolithiasis; calcium oxalate; herb; human; morbidity; nephrolithiasis; risk